Local Myocardial Contractility of the Left Ventricle in Patients with Ischaemic Heart Disease After Revascularisation - Nasyrova Zarina Akbarovna; Safarova Farangiz Hasanovna (Journal of Science in Medicine and Life, 2024)
Ischaemic heart disease is a major cause of morbidity and mortality in a worldwide epidemic. Myocardial ischaemia is characterised by an imbalance between myocardial oxygen delivery and myocardial oxygen demand, causing cardiac dysfunction, arrhythmias, myocardial infarction and sudden death. Various clinical manifestations of ischaemia are due to obstruction of coronary blood flow due to coronary stenosis, thrombosis and hyperconstriction (vasospasm) of epicardial and microvascular coronary arteries